THE ROLE OF DATA SECURITY IN THE WORLD OF EDUCATION TO INCREASE PARENTAL TRUST - Doton, Wlson (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
This study investigates the role of data security in enhancing parental trust within educational institutions. Employing a qualitative descriptive approach, data was collected through in-depth interviews with key stakeholders (principals, teachers, IT staff, and parents), direct observations of school environments, and analysis of relevant documentation. Thematic analysis revealed several key findings: Clear and comprehensive data security policies significantly contribute to parental trust. Active parental involvement in data security discussions fosters greater trust and understanding. Parental perceptions of data security directly influence their overall trust in the school. Challenges in implementing data security, such as budget constraints and staff training, require innovative solutions. The study emphasizes the need for a holistic approach to data security in education. By prioritizing data security, fostering open communication with parents, and addressing implementation challenges, schools can cultivate stronger trust, enhance student learning outcomes, and build a positive reputation within the community.